2014
DOI: 10.1136/bcr-2013-202039
|View full text |Cite
|
Sign up to set email alerts
|

Fatal hypertriglyceridaemia, acute pancreatitis and diabetic ketoacidosis possibly induced by quetiapine

Abstract: SUMMARYA 27-year-old man treated with quetiapine for anxiety disorder developed hypertriglyceridaemia-induced acute pancreatitis and diabetic ketoacidosis. He was otherwise physically healthy with no family history of hyperlipidaemia. Despite aggressive intensive therapy he died of multiorgan failure within 36 h from initial presentation. While second-generation antipsychotics are well known to be causally linked to diabetes and hyperlipidaemia, this is to my knowledge the firstdescribed case of a fatal triad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…There is no clear evidence of the benefit of insulin in HTG-AP for those patients who are not diabetic. By contrast, intravenous insulin is mandatory for those patients with type 1 diabetes mellitus who develop diabetic ketoacidosis and severe HTG with AP, which is not an uncommon association [56][57][58][59]. Nevertheless, insulin is also mandatory for patients with severe HTG and uncontrolled type 2 diabetes mellitus with [60] or without AP [61,62].…”
Section: Pharmacological Optionsmentioning
confidence: 95%
“…There is no clear evidence of the benefit of insulin in HTG-AP for those patients who are not diabetic. By contrast, intravenous insulin is mandatory for those patients with type 1 diabetes mellitus who develop diabetic ketoacidosis and severe HTG with AP, which is not an uncommon association [56][57][58][59]. Nevertheless, insulin is also mandatory for patients with severe HTG and uncontrolled type 2 diabetes mellitus with [60] or without AP [61,62].…”
Section: Pharmacological Optionsmentioning
confidence: 95%
“…Dysglycemia refers to abnormal blood sugar levels from any cause and is associated with increased morbidity and mortality. 1,2) Treatments involving gatifloxacin 3) (a novel fluoroquinolone antimicrobial drug) and olanzapine 4) and quetiapine 5) (atypical antipsychotic drugs) were previously found to induce severe dysglycemia; an Emergency Safety Information statement was issued in Japan, and the contraindication of these drugs for patients with diabetes melitus was added to package inserts. Ultimately, the oral dosage form of gatifloxacin was withdrawn from the market.…”
mentioning
confidence: 99%
“…Rashid et al reported a patient who developed pancreatitis and lifethreatening DKA while receiving ziprasidone 80 mg orally, twice daily, and quetiapine 200 mg orally, at bedtime for nine months (7). A 27-year-old man who was treated with quetiapine for anxiety disorder and developed hypertriglyceridemia-induced acute pancreatitis and DKA has been reported by Madsen KR from Denmark (8). The patient was otherwise physically healthy with no family history of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 95%